Analisis Efektivitas Sensus Pajak Bumi dan Bangunan Perkotaan dan Perdesaan (PBB- P2) dalam Rangka Meningkatkan Penerimaan Pajak Daerah di Kecamatan Mustikajaya Kota Bekasi - Putri Melati; Heksawan Rahmadi (Jurnal Ilmu Administrasi Publik, 2026)
The purpose of this study was to analyze the effective level of Land and Building Tax for Rural and Urban Areas (PBB-P2) is one of the main components of Local Own-Source Revenue (PAD) that plays an important role in supporting regional development financing. However, the realization of PBB-P2 revenue in Mustikajaya District, Bekasi City, during the 2019–2024 period has not yet achieved the established targets. This condition indicates the existence of problems in the management and optimization of regional tax potential. This study aims to analyze the effectiveness of the implementation of the PBB-P2 tax census, identify the inhibiting factors, and examine the efforts made to overcome these obstacles. The research uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The results show that the implementation of the PBB-P2 tax census in Mustikajaya District has not been fully effective. This is influenced by several factors, including low taxpayer awareness, limited human resources, technical constraints in data updating, and the suboptimal use of information technology in the regional tax system. Efforts made to address these obstacles include increasing public awareness through socialization programs, updating the tax database regularly, strengthening inter-agency coordination, and improving tax information systems. Therefore, more comprehensive and sustainable strategies are needed to enhance the effectiveness of the tax census and optimize PBB-P2 revenue as a source of local revenue.